Perancangan Small Private Space pada Interior Public Space di Perpustakaan Universitas Kristen Petra Surabaya - Lucky Basuki, Holiman Chandra Yusita Kusumarini (Intra, 2013)
Lifestyle of modern people use some time to move out of residence (public space) makes the most of the private activities can not be fulfilled. It is an idea and the idea of creating a space that can meet the needs of the private in public spaces with small dimensions. Private space in the design of the library is housed in Petra Christian University Surabaya as space scope of small private space (minimal private space dimension). The creation of small private space in the interior of the library can be considered fulfillment activity is private and academic support activities at the Library of Petra Christian University in Surabaya.Â Â